Stimuli-responsive/smart tablet formulations (under simulated physiological conditions) for oral drug delivery system based on glucuronoxylan polysaccharide. (2nd January 2020) - Muhammad, Gulzar; Haseeb, Muhammad Tahir; Hussain, Muhammad Ajaz; Ashraf, Muhammad Umer; Farid-ul-Haq, Muhammad; Zaman, Muhammad
Abstract: Objective: Development of stimuli-responsive intelligent drug delivery system (based on a polysaccharide, glucuronoxylan [GX]) with on-off switching properties under physiological conditions. Significance: As GX exhibits high swelling index and stimuli-responsive swelling/de-swelling properties, therefore, this material appeared highly useful to design pH, solvent and ionic stress-sensitive oral tablet formulations, which offered on-off switching properties. In this way, we could design intelligent/smart drug delivery systems for levosulpiride (LS) and theophylline (TF) with valuable pharmaceutical properties. Methods: GX-based tablet formulations were explored for stimuli-responsive, reversible swelling–deswelling behavior, dynamic swelling, and its kinetics. Tablet surface and channeling after swelling were observed using scanning electron microscopy (SEM). Drug release study was performed mimicking the physiological conditions like pH and transit time of gastrointestinal tract (GIT). Radiographic images of tablet path ( in vivo ) were recorded. Results: GX-based formulations exhibited high swelling in deionized water (DW), pH 6.8 and 7.4 while negligible swelling at pH 1.2. SEM images discovered the presence of microcracks and nanopores on the surface of tablets and showed channeling after swelling of tablets in DW. Sustained drug release was observed and found directly proportional to the concentration of GX in the formulations with negligible release at pH 1.2. In vivo radiographic evaluation indicated the retention of tablets in GIT for 7 h. Hemocompatibility studies showed the non-thrombogenic and non-hemolytic nature of GX. Conclusions: GX-based smart/stimuli-responsive formulations can control/sustain the release of drugs in GIT.